Cryo-Temperature Pretreatment Increases the Pro-Angiogenic Capacity of Three-Dimensional Mesenchymal Stem Cells the PI3K-AKT Pathway - Huasu Zhu; Yong Zhuang; Dong Li; Na Dong; Huixian Ma; Linghong Liu; Qing Shi; Xiuli Ju (Cell Transplantation, 2022)
To increase the potential and effectiveness of three-dimensional (3D) mesenchymal stem cells (MSCs) for clinical applications, this study explored the effects of short cryo-temperature pretreatment on MSC function. Adipose-derived MSCs (A-MSCs) were cultured via the ordinary monolayer method and 3D hanging drop spheroid method. When the cells adhered to the wall or formed a spheroid, they were subjected to hypothermic stress at 4°C for 1 h and then divided into three recovery periods at 37°C, specifically 0, 12, and 24 h. The control group was not subjected to any treatment throughout the study. Monolayer and 3D spheroid A-MSCs were analyzed via RNA sequencing after hypothermic stress at 4°C for 1 h. Subsequently, each group of cells was collected and subjected to phenotype identification via flow cytometry, and mRNA expression was detected via reverse transcription–quantitative polymerase chain reaction analysis. Western blot analysis was performed to analyze the PI3K-AKT signaling pathway in A-MSCs. The effects of A-MSCs on angiogenesis in vivo were examined using a chick chorioallantoic membrane assay. Transwell assays were performed to determine whether the culture supernatant from each group could induce the chemotaxis of human umbilical vein endothelial cells (HUVECs). Three-dimensional spheroid culture did not change the phenotype of A-MSCs. The expression of fibroblast growth factors, hepatocyte growth factors, and other angiogenesis-related factors in A-MSCs was upregulated. A-MSCs subjected to hypothermic stress promoted angiogenesis under both monolayer and 3D spheroid cultures. Moreover, the chemotaxis of HUVECs to the 3D spheroid culture supernatant increased substantially. Short cryo-temperature pretreatment could stimulate 3D spheroid A-MSCs and activate the PI3K-AKT pathway. This approach has the advantages of promoting angiogenesis and maintaining cell viability.